Medication-related inpatient falls: a critical review - Tatiane Bomfim Ribeiro; Daniela Oliveira de Melo; Flávia de Oliveira Motta Maia; Eliane Ribeiro (Universidade de São Paulo, 2018)
Abstract Falls are the second leading cause of accidental and unintentional injury deaths worldwide. Inpatient falls in hospital settings are likely to prolong the length of stay of patients in nearly 6.3 days, leading to increased hospitalization costs. The causes of fall incidents in healthcare facilities are multifactorial in nature and certain medications use could be associated with these incidents. This review seeks to critically evaluate the available literature regarding the relationship between inpatient falls and medication use. A comprehensive search was performed on MEDLINE, EMBASE and Lilacs with no time restriction. The search was filtered using English, Spanish or Portuguese languages. Our study evaluated medication use and inpatients falls that effectively happen, considering all ages and populations. An assessment of bias and quality of the studies was carried out using an adapted tool from the literature. The drugs were classified according to the Anatomic Therapeutics Chemical Code. The search strategy retrieved 563 records, among which 23 met the eligibility criteria; ninety three different pharmacological subgroups were associated with fall incidents. Our critical review suggests that the use of central nervous system drugs (including anxiolytics; hypnotics and sedatives; antipsychotics; opioids; antiepileptics and antidepressants) has a greater likelihood of causing inpatient falls. A weak relationship was found between other pharmacological subgroups, such as diuretics, cardiovascular system-related medications, and inpatient fall. Remarkably, several problems of quality were encountered with regard to the eligible studies. Among such quality problems included retrospective design, the grouping of more than one medication in the same statistical analysis, limited external validity, problems related to medication classifications and description of potential confounders.